2018
DOI: 10.1016/j.cmi.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicentre study of the epidemiology and outcomes of bloodstream infection in cirrhotic patients

Abstract: MDRO account for nearly one-third of BSI in cirrhotic patients, often resulting in delayed or inadequate empirical antimicrobial therapy and increased mortality rates. Our data suggest that improved prevention and treatment strategies for MDRO are urgently needed in the liver cirrhosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 21 publications
3
93
1
Order By: Relevance
“…Furthermore, the infectious episodes were, in the majority of cases, hospital acquired or healthcare related, due to MDR bacteria with a high rate of failure of the first empirical antibiotic treatment. This setting has been frequently reported in our country where the prevalence of infections from MDR bacteria is rather high …”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, the infectious episodes were, in the majority of cases, hospital acquired or healthcare related, due to MDR bacteria with a high rate of failure of the first empirical antibiotic treatment. This setting has been frequently reported in our country where the prevalence of infections from MDR bacteria is rather high …”
Section: Discussionmentioning
confidence: 76%
“…Here, we present a secondary analysis of the BICHROME study, a prospective multicenter study conducted in 19 tertiary centers from Italy (n = 10), Spain (n = 5), Germany (n = 2), Croatia (n = 1), and Israel (n = 1) from September 2014 to December 2015 designed to describe the current epidemiology of BSI in cirrhotic patients [6]. The core BICHROME study enrolled consecutive adult (aged >18 years) cirrhotic patients with BSI.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of liver cirrhosis was based on previous liver biopsy results or a composite of clinical signs and findings provided by laboratory test results, endoscopy, and radiologic imaging. Eligible patients were prospectively screened by study coordinators at each site through microbiological and admission records at the local liver units as previously described [6]. The study was approved by all local institutional review boards of the participating hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate initial antibiotic therapy has been demonstrated as the key independent factor of treatment outcomes in patients with Gram-negative bacteremia in previous studies from the adult ICUs or wards [11][12][13][14]. However, this issue has not been fully studied in the NICU, except for a small sample size, case-control study found in the literature [15].…”
Section: Introductionmentioning
confidence: 99%